Keefektifan konseling kelompok menggunakan teknik art therapy untuk meningkatkan student engagement Siswa Kelas IX SMP Negeri 22 Pontianak - Anysa, Fitri; Yuline, Yuline; Wicaksono, Luhur (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The research aims to test the effectiveness of group counselling services using art therapy techniques that is mindfulness based art therapy. The research method uses a quantitative approach with the Quasi Experimental Design, the One Group Pre-Test and Post-test Design research design. The sampling technique in this research is Purposive Sampling and the researchers obtained six pupils. In the data collection method used is by elevating student engagement. Then in the analysis techniques using presentation analysis and T-Test for Paired Sample. Group counselling activities were carried out with mindfulness based art therapy techniques divided into 9 sessions with evaluation at the last meeting. The results of the study showed that group counselling services using art therapy techniques were effective in improving student engagement, this was proven by the T-Test for Paired Sample with a value of t= -27,732 and a significance of 0,000<0,5 and the Effect Size calculation obtained a result of 11,406 >1,00 which belongs to the category of strong effects. (strong effect). Thus it was concluded that the provision of group counselling services using art therapy techniques provides a very strong effectiveness in increasing student engagement in the students of Class IX in the 22nd Pontianak state high school.